(untitled) (Journal of Enam Medical College, 2019)
Human immunodeficiency virus infection and acquired immune deficiency syndrome (HIV/ AIDS) is a global pandemic. According to Global HIV & AIDS statistics 2018, approximately 36.9 million people are living with HIV globally, 77.3 million [59.9 million–100 million] people have become infected with HIV since the start of the epidemic, 35.4 million [25.0–49.9 million] people died from AIDS-related illnesses since the start of the epidemic and 940000 [670000–1.3 million] people died from AIDS-related illnesses in 2017. It weakens a person’s immune system by destroying important cells that fight disease and infection. Dermatologic diseases are common in the HIV-infected population. Skin disease can be uniquely associated with HIV disease and many of the cutaneous diseases are not unique to this group, but the presentation can be more severe and recalcitrant to treatment. The spectrum of skin conditions includes skin findings associated with primary HIV infection and a broad range of skin problems related to the immune deficiency of advanced AIDS. Recognition of characteristic eruptions can facilitate early diagnosis of HIV. A broad variety of neoplastic, infectious and non-infectious diseases can manifest in the skin and may alert the clinician of declining of the immune system. This article reviews the current spectrum of HIV-associated skin conditions, focusing on common complaints, infections, drugassociated toxicity and malignancies based on recently published literature relevant to this area. J Enam Med Col 2019; 9(3): 185-188